Is Oral Candida associated with Dental Caries in Children - A Cross Sectional Analysis. - Mithun Pai; Shweta Yellapurkar; Srikant Natarajan; Ramya Shenoy (University Library System, University of Pittsburgh, 2022)
BACKGROUND: Dental caries is a world-wide public health issue and is considered the most common of all non-communicable disease. There has been a growing interest in association between oral fungal flora especially candida and dental caries. Hence the aim of the study was to assess the correlation between active caries status and oral candida carriage in children aged twelve years. MATERIALS AND METHODS: This is a cross-sectional study where a multiphase sampling was done and a total of thirty children were selected randomly among children screened previously. Data was collected through clinical oral examinations and structured interviews. The oral rinse technique described by Samaranayake et al. was used for extracting candida spp. The correlation between candida spplevel and caries experience was performed by the Pearsons correlation coefficient. RESULTS: The mean DMFS and defs scores of the children were 3.70±4.61 and 5.83±5.51 respectively. Significant association with decay scores for deciduous teeth (P<0.05) and defs (p= <0.001) was demonstrated. Candida species was associated highly with caries prevalence and significant positive correlation was found between Candida (CFU/plate) and defs scores (r=0.790) (p= <0.001) CONCLUSION: The study results suggested that there is a significant positive correlation between candida carriage and caries, especially in children in the age group of 12 years.